Oxytocin exposure in women with postpartum hemorrhage secondary to uterine atony - GROTEGUT, Chad A (2010)
OBJECTIVE: To determine if women with severe postpartum hemorrhage (PPH) secondary to uterine atony received greater amounts of oxytocin compared to women without PPH. STUDY DESIGN: Subjects with both severe PPH, defined as having received a blood transfusion, and PPH secondary to uterine atony were compared to matched controls. Total oxytocin exposure was calculated as the area under the concentration curve (mUnits/min*mins). Variables were compared using paired t-test, chi-square and logistic regression. RESULTS: Women with severe PPH had a mean oxytocin area under the curve (AUC) of 10,054 mU compared to 3762 mU in controls (p<0.001). After controlling for race, BMI, admission hematocrit, induction status, magnesium therapy, and chorioamnionitis using logistic regression, oxytocin AUC continued to predict severe PPH. CONCLUSION: Women with severe PPH secondary to uterine atony were exposed to significantly more oxytocin compared to matched controls.